POLITICS OF IDENTITY AND THE CASE OF AHOK’S RELIGION BLASPHEMY IN THE 2017 DKI JAKARTA ELECTION - Dalimunthe, Syairal Fahmy; Ardika, I Wayan; Putra, I Nyoman Darma; Suka Arjawa, I Gst. Bagus (E-Journal of Cultural Studies; Volume 13, Number 1, February 2020DO - 10.24843/cs.2020.v13.i01.p03, 2020)
Identity politics are often used in political contestation. Primordialism in similar religious and ethnic contexts creates the division and color of whose groups and supports whom. The purpose of this study is to understand and explain the politicization of religion and ethnicity in the DKI Jakarta 2017 elections. This study uses a cultural study approach with interpretive analysis techniques. The case of blasphemy by Ahok triggered the politicization of religion and ethnicity in the 2017 DKI Jakarta elections. Mass mobilization in the form of boycotts and the use of holy verses in choosing leaders was very massive carried out during the campaign period to increase the electoral effect. Identity is no longer purely a social movement to fight for a positive change, but rather a tool for the political elite to compartmentalize the masses in an effort to achieve their group goals. The identity politics that was triggered by the case of blasphemy by Ahok created a process of group exclusivity towards other groups on the basis of religion and ethnicity in winning a political battle.  Keywords: Identity politics, blasphemy of religion, Ahok, primordialism